Student Affairs Professionals at Catholic Colleges and Universities: Honoring Two Philosophies - Schaller, Molly A.; Boyle, Kathleen M. (Catholic Education: A Journal of Inquiry and Practice, 2006)
Student affairs professionals are encouraged by their professional organizations to recognize the responsibility they have to their institutions by “supporting its mission, goals and policies” (American College Personnel Association [ACPA], 2006, p. 6) and by avoiding conflicts of interest between the self and the college or university (national Association of Student Personnel Administrators [NASPA], 1990), others point out that most students affairs professionals are educated at secular universities and experience little preparation regarding the Catholic intellectual tradition (Estanek, 2001). The purpose of this study was to explore the following questions: Are there student affairs professionals at Catholic colleges and universities who are able to bring together a student affairs philosophy with that of catholic colleges and universities? If these professionals do exist, what can we learn from their knowledge and approaches that might help other student affairs professionals at Catholic colleges and universities to honor both philosophies? The results suggest that a great deal can be learned from seasoned professionals in Catholic student affairs, which may well assist new professionals in negotiating these two different philosophies.